Greenland, icebergs at Kjerulf Fjord and Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 31, 1931. Kjerulfs [Kjerulf] Fjord. Outer end. In background, first valley on west side Kjerulfs [Kjerulf] Fjord south of entrance at Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. See aerial K10 No. 28-10. This valley was starting point of J.M. Wordie and members of Cambridge Expedition on ascent of Petermann Peak. In background on extreme right is Riddarborgen (Peak) and S.S. Veslekari anchored just beyond right edge of photo. See Z-3. In foreground one of the largest icebergs of 525 or 530 in the fjord. See Aerial K 10 No. 19a - 7 for close up of this iceberg. Photo taken from motor-boat looking west.